Fungsi AIPA dalam Perwujudan ASEAN Community 2015 - Saptopo B. Ilkodar (Jurnal Paradigma, 2013)
ASEAN Inter-Parliamentary Assembly (AIPA) faces at least two challenges, its organizational structure and its performance. In the matter of organizational structure the members debate on the possibility to change AIPA from an assembly to be a parliament. As for the performance matter the members intend to increase its support to ASEAN in achieving ASEAN community targets. Considering Treaty of Amity and Cooperation (TAC) and the ASEAN way, the basic principles of ASEAN, the writer suggest AIPA to maintain its current structure while increasing the performance of the members national parliament respectively